Impact of school sports injury. Issue 4 (31st July 2003) - Abernethy, L; MacAuley, D
Abstract : Background: Most injuries in school occur during sport. Objectives: To explore the impact of sports injury in supervised school sport. Method: A prospective study of sports injury in children of secondary school age presenting to the accident and emergency department. Each patient was identified on registration, matched with medical records after discharge, and contacted later by telephone to complete a structured interview. Patients were only included if their injury was sustained during supervised school sport. Results: During the study period, 194 patients aged 11–18 attended the accident and emergency department with an injury, 51% of which occurred during school sport. Injuries occurred most commonly in rugby (43%), followed by physical education and games together (17.5%). Most injuries were x rayed (72%). Just over 12% of pupils lost no time from sport, most (71%) were back to sport within three weeks, and 2.7% were injured for more than eight weeks. Almost a third of parents needed to take time off from work to deal with the injured child. Conclusion: School sports injuries are important. They account for just over half of all injuries in secondary school children. They cause significant disruption to school and sport and have important implications for the wider family.